Hydro-morphologic setting of the Samborombón Bay (Argentina) at the end of the 21st century - Tosi, L. (2013)
We report on the hydrologic and morphologic setting of the Samborombón Bay, Argentina, which is expected at the end of the 21st century as a consequence of possible scenarios of relative sea level rise (RSLR). The geomorphological analysis of the Samborombón coastland points out only minor changes occurred over the last 40 yr. The modifications are mainly related to the construction of canals to enhance the floodplain drainage. A digital elevation model (DEM) obtained by the Shuttle Radar Topography Mission (SRTM) data archive, ad hoc calibrated/validated for the study area, highlights that about 3000 km2 of coastal plain present a morphological setting at high risk of sea flooding. The analysis of sea level and storm surge events recorded from 1905 to 2010 in Buenos Aires provides the RSLR rate and the return period of extreme floods. In addition, vertical land movements (VLM) measured by the permanent GPS stations of Buenos Aires and La Plata allow for the quantification of the eustatic component of the RSLR and estimating a plausible RSLR rate in the Samborombón Bay. Taking into account possible RSLR scenarios at the end of 2100 as resulting from the statistical analysis of (i) tide gauge and GPS time series and (ii) Intergovernmental Panel on Climate Change (IPCC) predictions, the potential effect of the increased sea level on the Samborombón coastland is simulated. The results show that the combined rise of sea levels, surficial waters and groundwater will lead to a new morpho-hydrologic setting of the coastal area, especially in the low-lying southern sector. Here, a coastline retreat up to 40 km is expected, with temporary submersion up to 4000 km2 during storm surges.